UROV DISEASE (KASHIN BECK DISEASE) AMONG CHILDREN IN TRANSBAIKALIA IN THE 2ND HALF OF THE XIX — EARLY ХХ CENTURIES - N.V. Eylbart (Вопросы современной педиатрии)
(Voprosy sovremennoi pediatrii = Current pediatrics. 2006;5(5):116-119)